Xingnaojing ameliorates synaptic plasticity and memory deficits in an Aβ1-42 induced mouse model of Alzheimer's disease - Yi Liu; Siyi Xu; Huijie Bian; Yi Qian; Huiya Li; Shu Shu; Jiang Chen; Xiang Cao; Yue Gu; Jiali Jin; Xi Zhang; Yun Xu; et al. (Elsevier, 2020)
The accumulation of insoluble amyloid β (Aβ) peptides is one of the pathological changes in Alzheimer's disease (AD), which induced synaptic plasticity impairment and excitatory amino acid toxicity associated with decreased memory function. Xingnaojing (XNJ), a well-known prescription in traditional Chinese medicine, has been used for the treatment of stroke for many years in China. In this study, we aim to investigate the therapeutic effects of XNJ in a hippocampus of Aβ1-42 induced mouse model of AD which showed significant memory loss and impaired synaptic morphology and function. Treatment of XNJ could attenuate spatial and working memory dysfunction, increase dendritic spine density and improve long-term potential (LTP) induction. In addition, XNJ treatment significantly increased the level of N-methyl-d-aspartate receptors (NMDARs) and inhibit the NMDA/α-amino-3-hydroxy-5-methyl-4-isoxazole propionate (AMPA) ratio in AD mice. XNJ treatment also activated the AKT/mechanistic target of rapamycin (mTOR) pathway, while inhibition of the mTOR pathway by rapamycin could reverse the protective effects of XNJ treatment. In conclusion, XNJ protected against synaptic plasticity and memory impairment in AD mice via the activation of AKT/mTOR signaling pathway, suggesting XNJ as an alternative treatment for AD.